The effect of annealing to the hardness of high Y2O3-Oxide dispersion strengthened (ODS) ferritic steels - Farha Mizana Shamsudin,; Shahidan Radiman,; Yusof Abdullah,; Nasri A. Hamid, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The purpose of this study was to investigate the effect of annealing to the hardness of high Y2O3-oxide dispersion strengthened (ODS) ferritic steels. The samples were prepared by mechanical alloying method followed by Cold Isostatic Pressing (CIP). After compaction process, the samples were sintered at 1100°C for 1 h in a tube furnace. The crystal structure and morphology of samples were analyzed by X-ray Diffraction (XRD) measurement and characterized by using field emission scanning electron microscope (FESEM), respectively. The hardness of samples was measured by using a micro-Vickers hardness tester with a load of 200 gf at annealing temperature of 600°C, 800°C and 1000°C, respectively. The Vickers hardness value (HV0,2) versus annealing temperature graph showed that the hardness of all samples started to decrease at temperature of 600°C due to grain growth. The hardness value of all samples (1Y and 5Y) identified at this annealing temperature is 855 HV0,2 and 808 HV0, 2, respectively.